Public attitudes, perceptions, and suggested strategies for managing free-roaming dogs in selected urban and rural settings in Uganda - Tayebwa, Dickson Stuart; Ssekandi, Colin; Nalubwama, Sylvia; Dankaine, Rogers; Lutebemberwa, Isa; Rashid, Njalira Kassim; Komugisha, Mariam; Bwambale, Kelvin; Katumba, Hannington; Kateregga, John; Muhangi, Denis; Biryomumaisho, Savino; et al. (Frontiers in Animal Science, 2025)
IntroductionUganda ranks among the top ten countries globally for reported dog bites, with an average of 14,865 cases annually, and records an estimated 486 human rabies deaths per year—partly due to the overwhelming number of free-roaming dogs (FRDs). Given that FRDs stem from societal mismanagement, sustainable control strategies must be rooted in meaningful community involvement. However, such community-based data remains largely unavailable in Uganda, hindering efforts to manage the growing FRD population.MethodsWe conducted a structured survey of 3,307 participants split between selected urban and rural areas in Uganda in 2023 to assess public attitudes and perceptions toward FRDs. Respondents were also asked to suggest appropriate control measures. We used chi-square tests to analyze sociodemographic differences and logistic regression to identify factors associated with attitudes toward FRDs.ResultsThe results showed that 81.9% of urban and 64.9% of rural respondents encountered FRDs daily. Attitudes toward FRDs were predominantly negative: 81.8% of respondents considered them a public health threat, and 57.1% viewed them as a nuisance. However, 76.3% also expressed empathy toward roaming dogs. Multivariable logistic regression analysis revealed that positive attitudes toward FRDs were associated with having a religious background, higher income, lower education levels, and residence in rural areas. Community-suggested control strategies included sterilization, public education on responsible dog ownership, and, controversially, poisoning.DiscussionThe findings highlight strong community awareness of the FRD issue, particularly as two of the top proposed measures—sterilization and public education—align with the World Organisation for Animal Health’s (WOAH) recommended strategies for managing roaming dog populations. Authorities can leverage the prevailing negative perceptions to design and implement humane, community-supported control strategies. Simultaneously, those who express empathy toward FRDs can be encouraged to translate their concern into proactive measures that reduce roaming behaviour.